Brain Structural Alterations in Left-Behind Children: A Magnetic Resonance Imaging Study - Fu, Yuchuan; Xiao, Yuan; Du, Meimei; Mao, Chuanwan; Fu, Gui; Yang, Lili; Liu, Xiaozheng; Sweeney, John A.; Lui, Su; Yan, Zhihan (Frontiers in Neural Circuits, 2019)
Parental migration has caused millions of children left behind, especially in China and India. Left behind children (LBC) have a high risk of mental disorders and may present negative life outcomes in the future. However, little is known whether there are cerebral structural alterations in LBC in relative to those with parents. This study is to explore the effect of parental migration on brain maturation by comparing gray matter volume (GMV) and fractional anisotropy (FA) of LBC with well-matched non-LBC. Thirty-eight LBC (21 boys, age=9.60±1.8yrs) and 30 non-LBC (19 boys, age=10.00±1.95yrs) were recruited and underwent brain scans in 3.0 T MR. IQ and other factors including family income, guardians’ educational level and separation time et al., were also acquired. Gray matter volume (GMV) and fractional anisotropy (FA) were measured for each participant and compared between groups using 2-sample t-tests with atlas-based analysis. Compared to non-LBC, LBC exhibited greater GMV in emotional and cortico-striato-thalamo-cortical circuits, and altered FA in bilateral superior occipitofrontal fasciculi and right medial lemniscus (P<0.05, Cohen's d>0.89, corrected for false-discovery rate). The increased GMV in bilateral parahippocampi was negatively correlated with IQ. Other factors including family income, guardians’ educational level and separation time were not associated with these brain changes. Our study provides empirical evidence of altered brain structure in LBC compared to non-LBC, responsible for emotion regulation and processing, which may account for mental disorders and negative life outcome of LBC. Our study suggests that absence of direct biological parental care may impact children's brain development. Therefore, public health efforts may be needed to provide additional academic and social/emotional supports to LBC when their parents migrate to seeking better economic circumstances, which has become increasingly common in developing countries.